The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1089/hum.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenovirus-Mediated Hepatocyte Growth Factor Gene Therapy on Postinfarct Heart Function: Comparison of Single and Repeated Injections

Abstract: Clinical trials testing the effects of a single injection of adenovirus carrying the human hepatocyte growth factor gene (Ad-HGF) in patients with chronic ischemic heart failure failed to show consistent improvements in cardiac function. The aim of this study was to evaluate the efficacy of repeated injections of Ad-HGF in a rat model of postinfarct heart failure. Ad-HGF or Ad-green fluorescent protein (GFP) was administered to Sprague Dawley rat models of postinfarct heart failure via single or fractional rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…HGF is a multi-functional growth factor with anti-inflammatory and angiogenic activities [31]. Currently, clinical trials of the HGF gene therapy in the treatment of ischemic heart failure are ongoing [32]. Coupling the HGF gene therapy and cell therapy displayed a synergistic promoting effect on tissue regeneration and therapeutic angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HGF is a multi-functional growth factor with anti-inflammatory and angiogenic activities [31]. Currently, clinical trials of the HGF gene therapy in the treatment of ischemic heart failure are ongoing [32]. Coupling the HGF gene therapy and cell therapy displayed a synergistic promoting effect on tissue regeneration and therapeutic angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HGF administration was effective and safe in other preclinical studies [ 9 , 13 , 50 ]. Consequently, there are various clinical trials at present in which patients are recruited for assessment of HGF administration by different routes [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the c-Met receptor further activates many intracellular signalling pathways, including RAS-mitogen activated protein kinase, signal transducer and activator of transcription, phosphatidylinositol-3 kinase, protein kinase B, mammalian target of rapamycin, and β-catenin pathway [33,34]. Our group has previously shown that HGF therapy could promote cardiac repair and improve cardiac function in MI rats through the above mechanisms [35].…”
Section: Discussionmentioning
confidence: 99%